The Effect of Emotional Intelligence on Employee Performance Through Work Ability as a Mediating Variable - Abdul Rasyid; Mansur Mansur; Muhdi Ibrahim; Zakaria Zakaria; Olivia Sesilia Aronggear; Andri Irawan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to examine the effect of Emotional Intelligence on employee performance with work ability as a mediating variable. Using an explanatory quantitative approach, data were collected through a questionnaire with 12 interval scale statements from 117 office employees randomly selected from a population of 123 employees. The analysis was conducted using SPSS 24 and AMOS 24 software, applying Structural Equation Modeling (SEM) and the Sobel test. The results showed that Emotional Intelligence significantly improved employee performance directly and strengthened work ability, which in turn had a positive impact on performance. Work ability significantly mediated the Emotional Intelligence -performance relationship, strengthening the influence of Emotional Intelligence through increased task competence and emotional resilience. These findings confirm the role of Emotional Intelligence in driving work effectiveness and overcoming performance challenges. In conclusion, organizations need to integrate KE and work ability training to improve employee work outcomes and service quality, providing practical insights for PT PLN to improve operational effectiveness and public trust.